Answer:
5,120
Step-by-step explanation:
an = 5.(-2)^(n-1)
a11 = 5.(-2)^(11-1)
= 5.(-2)^10
= 5.(1,024)
= 5,120
Answer:
x=0.9
Step-by-step explanation:
1.convert to improper fractions
4x+9/7/3=3x/0.5
2.Apply fraction cross multiply
(4x+9) * 0.5=7/3 * 3x
3. simplify
(4x+9) *0.5 =7x
4.Expand
2x+4.5=7x
5.Subtract 4.5 from both sides
2x=7x-4.5
6.Subtract 7x from both sides
2x-7=7x-4.5-7x
7.Simplify
-5x=-4.5
7.Divide by -5
x=0.9
Answer:
Yes
Step-by-step explanation:
4 < 3(2) + 6
4< 6+6
4 < 12
Substract 6 to both sides and you get 36 =-2d then you use the multiplicative inverse and d=-18.
Assuming your solving for y:
py+7=6y+q
-6y -7 -6y -7
(p-6)y = q-7
divide both sides by p-6
y=(q-7)/(p-6)